2021
DOI: 10.3389/fcimb.2021.635673
|View full text |Cite
|
Sign up to set email alerts
|

Two Acinetobacter baumannii Isolates Obtained From a Fatal Necrotizing Fasciitis Infection Display Distinct Genomic and Phenotypic Characteristics in Comparison to Type Strains

Abstract: Acinetobacter baumannii has been recognized as a critical pathogen that causes severe infections worldwide not only because of the emergence of extensively drug-resistant (XDR) derivatives, but also because of its ability to persist in medical environments and colonize compromised patients. While there are numerous reports describing the mechanisms by which this pathogen acquires resistance genes, little is known regarding A. baumannii’s virulence functions associated with rare manifestations of infection such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…This type of wound requires dressings that have an anti-bacterial effect and can absorb purulent exudate. In this study, it was found that 76.4% of patients with wound dressing therapy only after debridement necrotomy surgery, and 24% of patients with CNF received further reconstructive surgery therapy after debridement necrotomies and the use of wound dressings when the wound bed was good and general condition was stable (Grier, 2021).…”
Section: Discussionmentioning
confidence: 75%
“…This type of wound requires dressings that have an anti-bacterial effect and can absorb purulent exudate. In this study, it was found that 76.4% of patients with wound dressing therapy only after debridement necrotomy surgery, and 24% of patients with CNF received further reconstructive surgery therapy after debridement necrotomies and the use of wound dressings when the wound bed was good and general condition was stable (Grier, 2021).…”
Section: Discussionmentioning
confidence: 75%
“…Biofilm forming is an important virulence factor for bacterial pathogen [ 25 ]. Based on crystal violet staining and SEM analysis, exposure to 0.1–10 μg/L NPs did not affect the amount of biofilm formation of A. johnsonii AC15 ( Figure 5 A–C).…”
Section: Resultsmentioning
confidence: 99%
“…The 96 well microtiter plate assay was used to evaluate biofilm formation [ 25 ]. In each well, 100 μL NPs (0.1–1000 μg/L) and 10 μL A. johnsonii AC15 were added.…”
Section: Methodsmentioning
confidence: 99%
“…Non-device-related infections also have a significant impact on health problems. Dental plaque ( Rabe et al., 2022 ), urinary tract infections ( Singh et al., 2022 ), cystic fibrosis ( Vandeplassche et al., 2020 ), otitis media ( Bair et al., 2020 ), infective endocarditis ( Han and Poma, 2022 ), tonsillitis ( Klagisa et al., 2022 ), periodontitis ( Prado et al., 2022 ), necrotizing fasciitis ( Grier et al., 2021 ), osteomyelitis ( Huang et al., 2022 ), infective kidney stones ( Fayez Hassan et al., 2021 ), chronic inflammatory diseases ( Wu et al., 2015 ), bacterial vaginitis ( Arroyo-Moreno et al., 2022 ), and bladder infections ( Mirzaei et al., 2020 ) are all examples of non-device-related bacterial biofilm infections.…”
Section: Biofilm-associated Infectionmentioning
confidence: 99%